Catheter Ablation of Paroxysmal Atrial Fibrillation Initiated by Non–Pulmonary Vein Ectopy - Wei‐Shiang Lin; CHING‐TAI TAI; Ming-Hsiung Hsieh; Chin-Feng Tsai; Yung‐Kuo Lin; Hsuan-Ming Tsao; Jin‐Long Huang; Wen‐Chung Yu; Shih-Ping Yang; Yu-An Ding; Mau-Song Chang; Shih‐Ann Chen (2003)
Background— Most of the ectopic beats initiating paroxysmal atrial fibrillation (PAF) originate from the pulmonary vein (PV). However, only limited data are available on PAF originating from the non-PV areas. Methods and Results— Two hundred forty patients with a total of 358 ectopic foci initiating PAF were included. Sixty-eight (28%) patients had AF initiated by ectopic beats (73 foci, 20%) from the non-PV areas, including the left atrial posterior free wall (28, 38.3%), superior vena cava (27, 37.0%), crista terminalis (10, 3.7%), ligament of Marshall (6, 8.2%), coronary sinus ostium (1, 1.4%), and interatrial septum (1, 1.4%). Catheter ablation eliminated AF with acute success rates of 63%, 96%, 100%, 50%, 100%, and 0% in left atrial posterior free wall, superior vena cava, crista terminalis, ligament of Marshall, coronary sinus ostium, and interatrial septum, respectively. During a follow-up period of 22±11 months, 43 patients (63.2%) were free of antiarrhythmic drugs without AF recurrence. Conclusions— Ectopic beats initiating PAF can originate from the non-PV areas, and catheter ablation of the non-PV ectopy has a moderate efficacy in treatment of PAF.